If it's not what You are looking for type in the equation solver your own equation and let us solve it.
96=6(7+3x)
We move all terms to the left:
96-(6(7+3x))=0
We add all the numbers together, and all the variables
-(6(3x+7))+96=0
We calculate terms in parentheses: -(6(3x+7)), so:We get rid of parentheses
6(3x+7)
We multiply parentheses
18x+42
Back to the equation:
-(18x+42)
-18x-42+96=0
We add all the numbers together, and all the variables
-18x+54=0
We move all terms containing x to the left, all other terms to the right
-18x=-54
x=-54/-18
x=+3
| x^2+18x-73=-10 | | (2x+51)(5x+4)=90 | | 3x3–81=0 | | 10x-3+4x+2+9x-13=180 | | 2e²-3e+1=0 | | (x+5)x2=19 | | u/6−-65)=75 | | 6/8=57/x | | 10x-2=0.5(27x+3-9x-5) | | 8(2v+2)=4(4v+3)+4 | | x/4+15=33 | | 8x1=15 | | 8x+3+10x−7=180 | | -5x-8=41+2x | | 200+40x=120+50x | | x^2+18x+73=-10 | | x+5x2=19 | | 2e^2-3e+1=0 | | 2/5h+1/5h=-35/3 | | 2,000(x-24)+5,000=18,000 | | u/6−(–65)=75 | | 1a+1a=5 | | d.10=20d= | | 5/2x+1/5x=41/2+7/2x | | 4x+80=152 | | 3(2x+x)-3x=12. | | 7(x+2)=10=7x+4 | | 19x-2-105=16x+2 | | 2x-6/5=8 | | 3m-6+2m-4= | | 2(2x-1)+3(x+2)+x=48 | | 4t-15=33 |